Dental management of a patient with systemic mastocytosis. Issue 4 (15th April 2022) - Legge, Alexander Richard; Whyte, Andrew; Heywood, Simon
Abstract : Mastocytosis is a term encompassing a group of clinical disorders characterised by clonal proliferation of abnormal mast cells (MCs) in organ systems of the body. Mastocytosis can be systemic (with or without skin involvement) or cutaneous, and can affect organs including bone marrow, liver, spleen, lymph nodes and mucosal surfaces. Patients with systemic mastocytosis (SM) are susceptible to triggers that could cause activation of abnormal MCs, resulting in multiorgan dysfunction and life-threatening anaphylactic reactions. Mastocytosis has a number of ramifications for the dental management of a patient with the condition. Patients are at increased risk of complications due to a number of risk factors for MC activation present within the dental context, including stress, certain prescribed drugs, oral hygiene products and dental materials. This report presents the oral management of an adult with SM, discussing the implications of the condition within the context of the limited existing literature on the subject.